Website Quality and Marketing Communication Create Purchase Decisions At Tiga Negeri Music House Store Bandung - Ine Aprianti; Taufik Zulfikar; Gusti Nugraha; Lucy Nurfadilah; Rika Kartika (Institute of Computer Science (IOCS), 2022)
The development of communication and information technology that is growing has led to increasingly varied marketing methods. Currently, in addition to conventional marketing methods, business people also do online marketing. The Tiga Negeri Music House store, located in the city of Bandung, also conducts online marketing in addition to conventional marketing. Online marketing is done by using the media website, but the development of marketing using the website over the last few years has been less than encouraging. Utilization of the website in supporting the improvement of product and service marketing is a must and something that is commonly done today. The purpose of this study is to analyze and examine the influence of website quality and marketing communication on purchasing decisions either partially or simultaneously. The method used is quantitative. Multiple linear regression was used in this study to analyze the data. The sample is 100 people who are consumers. The results showed that there was a positive and significant influence on website quality and marketing communication on purchasing decisions either partially or simultaneously.